Pengembangan Bahan Ajar Berbasis Multimedia Interaktif Dalam Meningkatkan Minat Belajar Matematika Siswa - Rizqi Nuritno; Hendri Raharjo; widodo winarso (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2017)
This research is a form of interactive multimedia development as a resource that aims to: 1) Develop Interactive Multimedia Learning Material and Beam Cube; 2) Determine the feasibility of Cube Interactive Multimedia Learning Material and Beam; 3) Increasing interest in learning math using the Interactive Multimedia Learning Material and Beam Cube. This research method is the Research and Development (R & D), adapted from ADDIE development model, with the following steps: 1) Analysis,2) Design,3) Development,4) Implementation5) Evaluation.Validation is done by two people matter experts and two experts media. Teaching materials developed tested to 5 learners VIII class A and 31 learners in class VIII B of SMP Negeri 12 Cirebon. Feasibility level Interactive Multimedia-Based Instructional Materials and Beam Cube based assessment: 1) Matter Experts obtained an average value of 4.2 which is included in the category of Good, 2) Expert Media obtained an average value of 4.26 are included in the category of Very Good, 3) learners field trials obtained an average value of 4.26 are included in the category of Very Good. Thus the Interactive Multimedia-Based Instructional Materials and Beam Cube is good and fit for use as teaching material. Based on the analysis Interest in Learning students before and after the use of the Interactive Multimedia-Based Instructional Materials and Beam Cube, obtained by N-gain of 0.405 which is included in the category of Medium of the total score early 2026 into 2521. In the test paired t test obtained t count equal to -16.619 with sig , 0,000 showed significant measurement so that the conclusion is the development of Interactive Multimedia-Based Instructional Materials and Beam Cube can improve Students Interest in Learning Mathematics.